Impact of electrolyte-permeable microcracks in secondary particles on performance of high nickel layered oxides: negative or positive?. (March 2022) - Tan, Xinghua; Zhao, Tingqiao; Guo, Limin; Mao, Dongdong; Song, Luting; Liu, Guangyao; Wang, Hanfu; Chu, Weiguo
Abstract: Generation of electrolyte-permeable microcracks in cycled secondary particles is normally considered to play a negative role in capacity fading for Ni-rich layered oxides. Here, the unambiguous role of electrolyte-permeable microcracks in capacity fading of LiNi0.8 Co0.15 Al0.05 O2 (NCA) and LiNi0.8 Co0.1 Mn0.1 O2 (NCM811) against cycling was recognized by exploring the performances of their pristine secondary particles and artificially pre-cracked/broken ones. Intriguingly, the artificially pre-cracked NCA and NCM811 show higher capacity retentions than those of the pristine ones after 200 cycles although almost no microcracks were observed in both the initial and cycled states after 200 times for the pristine samples. Moreover, even more serious negative effects of side reactions, phase transitions, and dissolution of transition metals which are normally believed to degrade the cycling performance were clearly found in the cycled pre-cracked/broken samples. This is indeed beyond conventional recognition. Their better cycling performance for 200 cycles is a result of fewer Li vacancies and inactive Li sites. This new finding may trigger a reinvestigation of the role of electrolyte-permeable intergranular cracks in the cycling performance of nickel-rich layered oxides and other materials for the exploration of novel performance-improved strategies. Graphical abstract: Image 1 Highlights: NCM811 and NCA secondary particles are in-situ pre-cracked by pressing their films. Electrolyte-permeable pre-cracks can alleviate capacity fade against cycling. Improved cycling stability is due to the suppression of Li vacancies by pre-cracks. A unique approach is proposed for correlating performance and pre-cracking. Pre-cracking of secondary particles is a new strategy for improving performance.